Invasive lobular carcinoma with extracellular mucin as a distinct variant of lobular carcinoma: a case report - Haltas Hacer; Bayrak Reyhan; Yenidunya Sibel; Kosehan Dilek; Sen Meral; Akin Kayihan (BMC, 2012)
Abstract The differences between invasive lobular and ductal carcinomas affect the diagnostic and therapeutic management for patients with breast cancer. In most cases, this can be accomplished because of distinct histomorphologic features. However, occasionally, this task may become quite difficult, in particular when dealing with the variants of infiltrating lobular carcinoma. Lobular carcinoma has been considered a variant of mucin-secreting carcinoma with only intracytoplasmic mucin. The presence of extracellular mucin is a feature of ductal carcinoma. Herein is presented a case of lobular carcinoma with extracellular and intracellular mucin in a 43-year-old female patient, and confirmed by immunohistochemistry. Up to the present, infiltrating lobular carcinoma displaying extracellular mucin has not been described in the literature except two case. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1839906067716744